Dampak Sosial Media Marketing Uniqlo Terhadap Perilaku Pembelian Remaja - Gresselya Limbong; Afsya Khairia; Lestari Siringo Ringo (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to analyze the influence of social media marketing on purchasing decisions for Uniqlo products in Indonesia, considering the mediating role of influencers in the Generation Z era. Using a quantitative approach, data was collected through an online questionnaire via Google Forms from 104 respondents who are active students in Medan City and have made purchases through social media platforms. Data analysis included validity tests, reliability tests, classical assumptions, multiple linear regression, F tests, t tests, and Sobel tests. The results showed that social media marketing significantly influences purchasing decisions, with Uniqlo's content on social media and promotional appeal as the main significant variables. However, the frequency of viewing content did not have a significant effect. This influence was strengthened by the role of influencers as mediators. The conclusion emphasizes the importance of digital marketing strategies to maintain brand existence, with suggestions for Uniqlo to increase the use of platforms such as TikTok and Twitter to reach a wider audience. This study provides insights for fashion brands in building emotional connections with Gen Z consumers.